The Patriarchal Interpretation and the Political Participation of Rural Women in Bondowoso East Java - Bahar, Moh. Syaeful; Harnadi, Dodik; Sa’diyah, Zaimatus (Institut Agama Islam Negeri Madura, 2022)
This study aims to oversee the practice of gender injustice that affects rural women's lack of substantive political participation in Bondowoso Regency. During the Legislative General Election in 2014-2019 and 2019-2024, women's political participation was complimentary for the registration and administrative requirements rather than substantial involvement. This situation continues to happen even after the release of regulations that require the fulfillment of a quota of 30 percent of women’s representation in a political party. This study uses a qualitative approach. Furthermore, this study also uses a feminist approach. By using that feminist approach, this study aims to discover (1) how rural women in Bondowoso respond to political engagement and (2) how religious arguments are interpreted concerning the role of women in political engagement. This study found that (1) women’s involvement in politics is high in quantity rather than quality. Women’s political participation does not directly guarantee their active role in the political world. Instead of making a maximum contribution to the development of politics, women’s participation is stigmatized. (2) One circumstance that hinders women’s participation relates to the misogynistic interpretation of religious teachings in Bondowoso’s rural society. It refers to patriarchal domination in understanding the concept of leadership in Islam that eventually stigmatizes women’s involvement in politics.